2006
DOI: 10.3998/ark.5550190.0007.408
|View full text |Cite
|
Sign up to set email alerts
|

The reductive decyanation reaction: chemical methods and synthetic applications

Abstract: Several sequences involving the nitrile group require the removal of this function in a convenient and clean procedure. This transformation, called reductive decyanation, has received much attention over the years. In this review, we describe the chemical methods leading to reductive decyanation as well as the proposed mechanisms. Much of these methodologies proceed with good yields and stereoselectivities allowing their exploitation in organic synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…The utility of nitriles as functional handles and activating groups is crucial to the strategic deployment of carbon–carbon bond-forming reactions. , Though nitriles are valuable for their ability to facilitate carbon–carbon bond formation, the nitrile functionality is not always desired in downstream adducts. Excising a nitrile group by a reductive decyanation allows for the use of nitriles as traceless functional handles for assembling molecular complexity . In the past decade, several methods for transition-metal-catalyzed reductive decyanation reaction have been developed .…”
mentioning
confidence: 99%
“…The utility of nitriles as functional handles and activating groups is crucial to the strategic deployment of carbon–carbon bond-forming reactions. , Though nitriles are valuable for their ability to facilitate carbon–carbon bond formation, the nitrile functionality is not always desired in downstream adducts. Excising a nitrile group by a reductive decyanation allows for the use of nitriles as traceless functional handles for assembling molecular complexity . In the past decade, several methods for transition-metal-catalyzed reductive decyanation reaction have been developed .…”
mentioning
confidence: 99%
“…The reductive decyanation of α‐aminonitriles consists of the neat replacement of the nitrile group by a hydrogen atom [37] . In light of our previous experiences, this process can be efficiently performed by stirring a mixture of α‐aminonitrile 12 a and NaBH 4 in ethanol at ambient temperature for 12 h. After treatment, the expected tertiary amine 13 a was recovered in a poor 30 % yield, and these findings suggest that the cleavage of the C−CN bond does not provide the intermediary iminium ion.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of compounds 5a and 5h showed that, although both azonine rings adopt a different conformation, the lone pair at the pyramidal ring nitrogen is oriented anti­peri­planar to the nitrile group in both cases (see Supporting Information). This should make di­benzazo­nine carbonitriles of type 5 suitable candidates for substitutions of cyanide in elimination/addition reactions, such as the Bruylants reaction or reductive decyanations. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…This should make dibenzazonine carbonitriles of type 5 suitable candidates for substitutions of cyanide in elimination/addition reactions, such as the Bruylants reaction or reductive decyanations. 30,31 To test this hypothesis, compound 5a was treated with LiAlH 4 to obtain the decyanated dibenzo[c,f ]azonine 7 in 84% yield (Scheme 5).…”
Section: Scheme 3 [14]-sigmatropic Rearrangement Of the Tetrahydroiso...mentioning
confidence: 99%